Intravenous Tramadol Injection has no Antinociceptive Effect in Horses Undergoing Electrical and Thermal Stimuli - Santi Milaré, Anelize; de Oliveira, Flávia Augusta; Luna, Stélio Pacca Loureiro [UNESP]; Rizzo Scognamillo, Márcia Valéria; de Queiroz-Neto, Antonio (Elsevier, 2013)
Tramadol combines an μ opiate and nonopiate analgesic mechanism and might be a useful opioid in horses. This study evaluated the effect of IV tramadol on spontaneous locomotor activity (SLA), head height, and hoof withdrawal reflex (HWR) after thermal or electrical nociceptive stimuli in horses. Doses of 2 and 3 mg/kg tramadol did not affect HWR after electrical and thermal nociception, respectively. Head height and SLA were not modified by 2, 3, or 5 mg/kg tramadol. All horses treated with 5 mg/kg tramadol developed trembling in pectoral triceps, and gluteal muscles and adopted a base-wide stance. In conclusion, 2 and 3 mg/kg tramadol IV neither induced sedation nor prolonged HWR after thermal or electrical stimuli in conscious horses. The dose of 5 mg/kg tramadol IV produced excitement, and it is apparently unsuitable for clinical use. © 2013 Elsevier Inc. All rights reserved.
Keywords: Antinociception; Horses; Opioid; Spontaneous locomotor activity